Explaining the Popularity of Integrity Policies in Times of Critical Governance—The Case of Conflicts of Interest Policies for Ministers in the EU-Member States. (2nd January 2023) - Demmke, Christoph; Autioniemi, Jari; Lenner, Florian
Abstract: Current critical governance trends raise important questions for scholars in the field of integrity policies. Currently, scholars agree that governance trends show declining trends in the fields of democracy, human rights, justice, rule of law, corruption, conflicts of interest, politicization, protection of privacy, equality, and freedom of the press. These trends exist in many countries, albeit to a different degree. On the other hand, one can also observe an expansion of integrity policies. In the field of conflicts of interest (CoI), for more than a decade, CoI-policies have become ever more comprehensive and sophisticated. Countries implement ever more policies, introduce stricter standards and invest more in the implementation of CoI policies. CoI policies become more complex and the institutionalization and management of CoI policies more professional. In view of these seemingly paradoxical trends, the purpose of this article is to discuss the relationship between these critical Governance trends and integrity policies. We discuss the case of conflict of interest policies for Ministers/Secretaries. We conclude that trends toward critical governance fit with the expansion of integrity policies for various reasons, but mostly because they are (increasingly) used as useful political instruments for various political interests.